Efeito das paisagens modificadas por práticas agrícolas sobre a composição e estrutura das assembléias e espécies de Drosophilidae (Diptera) - FURTADO, Ivaneide da Silva (Universidade Federal do Pará, 2017)
The Amazon Rainforest holds the largest biodiversity in the world. It occupies more than 40% of the Brazilian surface. In recent years the rates of forest loss and degradation of Amazonia have considerably increased as a result of agricultural expansion, creating a mosaic of highly modified landscapes. These changes endanger both biodiversity and ecosystem services associated with it, besides causing severe stress on the species. Effects of stress can result in physiological changes that are reflected in morphological differentiation among remnant populations, which now occupy the new landscape. The objective of this study was to test the effect of some types of land use on the assembly of frugivorous Drosophilidae and on the morphology of some species originally settled within the forest areas that have become a patchwork landscape containing forest fragments, ecological succession and crop zones. The first study was conducted in three agricultural villages and the second within six locations, including three preserved forest areas. Sampling was performed in a standardized manner, with traps placed along the established transects on the use of predominant land within the area of study. Our results showed that the richness of the species did not differ between different types of land use, but the distributions and abundances of the species' composition were clearly distinct between intensive agricultural uses and forest systems. The forest's coverage and the relative humidity were the variables determining the distribution of the species. The agricultural uses were characterized by cosmopolitan non-native species associated with more open areas. There were found morphological differences between the individuals caught in the areas of preserved forest and agricultural use zones, regardless of the species. Surprisingly, the number of individuals captured in the forests was always lower compared to those captured in the more intensive types of use. These results show the effects of landscape mutation on the remaining populations of native species, indicating the range of quantitative and qualitative alterations on the set of species. However, the maintenance of the forest patches on areas of agricultural use can benefit the permanency of native species in these landscapes.